Mediating role of lean manufacturing practice for information technology resources and performance improvement of manufacturing firms - Ghobakhloo, Morteza (2015)
The computer-based Information Technology (IT) is a major technological innovation that has been vastly adopted by organizations to achieve performance improvement. Understanding how performance of firms, at the organizational level of analysis, is affected by IT and relative systems is an important and cutting-edge research topic. Recent IT business value scholars drew on the resource-based view of the firm and proposed that IT has an indirect, not a direct, impact on business performance through IT-enabled capabilities. The present study draws on the so-called IT-enabled capabilities perspective to study the relationships between IT, lean manufacturing and business performance improvement to shed more light into relationship between IT and business performance improvement among manufacturing firms. Therefore, the present study mainly aims to examine whether the application of current IT and different principles of lean manufacturing are interdependent and complementary or they are mutually exclusive. Using a questionnaire-based survey, the study collected from 131 leading Iranian and 125 Malaysian manufacturers to test the proposed research model of lean manufacturing sustainability using Partial Least Square-Structural Equation Modeling (PLS-SEM). The study also benefits from a two years longitudinal case study to assess the applicability of proposed model. Finding shows that lean manufacturing and IT are mutually interdependent and value of IT resources can be effectively transformed into business performance improvement for manufacturers through the higher levels of lean manufacturing sustainability. In effect, IT-enabled lean manufacturing sustainability accounted for 41.3% of variance in business performance improvement. Advanced manufacturing technology competency is a valuable intermediate capability which links IT investments into lean manufacturing sustainability. Findings also show that IT resource is one of the minimum requirements of lean manufacturing for surveyed business, and the value of IT investment is truly transformed to valuable capability when IT investments and resources offer competent administrative advanced manufacturing technologies for effective management of all production processes.